1994
DOI: 10.1017/s0022377800017499
|View full text |Cite
|
Sign up to set email alerts
|

Reflection and excitation of ion-acoustic waves in a multi-component plasma with negative ions

Abstract: Reflection and excitation of ion-acoustic waves by a bipolar potential structure consisting of a grid and a metallic plate have been investigated experimentally in a multi-component plasma with negative ions. Reflection is observed owing to the presence of the negative ions, even if both the grid and the plate are biased negatively with respect to the plasma potential so as to collect positive ions. Reflection coefficients and excitation efficiencies are measured as a function of the bias voltage of the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Linear ion acoustic waves were reflected from a positively biased solid metallic plate. 9 KdV solitons were reflected from a negatively biased metal plate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] Linear ion acoustic waves were reflected from a positively biased solid metallic plate. 9 KdV solitons were reflected from a negatively biased metal plate.…”
Section: Introductionmentioning
confidence: 99%
“…Ito and Nakamura observed the reflection of linear ion acoustic waves in the bipolar potential structure, even though both the grid and the plate were biased negatively, and explained that the reflection took place because the negative ions were repelled by the structure. 21 Cooney et al investigated the reflection of rarefactive KdV solitons from a negatively biased plate and found out that the point of reflection shifted away from the plate and the shift was proportional to ͉V bias ͉ 3/4 , where V bias is the bias voltage applied to the metal plate. 22 This suggested that the reflection occurs at the edge of the Langmuir sheath.…”
Section: Introductionmentioning
confidence: 99%